Association of sella turcica bridging and morphologic characteristics with palatally impacted canine in lateral cephalograms - Nikoo Ghasemi; Soraya Akhoondi; Zohre Reyhani; Nima Motamed; Azin Nourian (Dentistry 3000, 2022)
Introduction: Researchers have been interested in the relationship between sella turcica bridging and various dental anomalies. This study investigates the association of sella turcica bridging and morphologic characteristics with the palatally impacted canine tooth.